Biallelic Mutations in MYORG Cause Autosomal Recessive Primary Familial Brain Calcification - Yao, Xiang-Ping; Cheng, Xuewen; Wang, Chong; Zhao, Miao; Guo, Xin-Xin; Su, Hui-Zhen; Lai, Lu-Lu; Zou, Xiao-Huan; Chen, Xue-Jiao; Zhao, Yuying; Dong, En-Lin; Lu, Ying-Qian; et al. (Neuron (Cambridge, Mass.), 2018)
Primary familial brain calcification (PFBC) is a genetically heterogeneous disorder characterized by bilateral calcifications in the basal ganglia and other brain regions. The genetic basis of this disorder remains unknown in a significant portion of familial cases. Here, we reported a recessive causal gene, MYORG, for PFBC. Compound heterozygous or homozygous mutations of MYORG co-segregated completely with PFBC in six families, with logarithm of odds (LOD) score of 4.91 at the zero recombination fraction. In mice, Myorg mRNA was expressed specifically in S100β-positive astrocytes, and knockout of Myorg induced the formation of brain calcification at 9 months of age. Our findings provide strong evidence that loss-of-function mutations of MYORG cause brain calcification in humans and mice. •MYORG is a major causal gene for autosomal recessive PFBC•Specific expression of MYORG suggests astrocyte involves in PFBC•Myorg knockout mice develops calcium deposits in the brain Yao et al. provide evidence that MYORG is a major causal gene for autosomal recessive PFBC by a comprehensive strategy combining whole-exome sequencing analysis, Sanger sequencing, linkage analysis, RNA expression analysis, and a mouse model.